Optimizing spacing and fertilization to maximize yield and quality of tropical sugar beet (Beta vulgaris L.) in Bangladesh - Md. Abu Taher Sohel; Tasfiqure Amin Apon; Himadri Prosad Roy; Md. Kamruzzaman; Md. Abdul Kader (Fundamental and Applied Agriculture)
Sugar beet, a potential sugar crop in Bangladesh needs to develop appropriate agronomic package to get maximum yield and quality. Therefore, to study yield and quality of sugar beet as influenced by spacing and fertilization, an experiment was conducted at the Bangladesh Sugarcrop Research Institute (BSRI) farm, Ishurdi, Pabna, during 2019-20 cropping season. To select the most suitable spacing and fertilizer dose, the experiment was carried out in RCBD using two spacing, viz., S1: 50 cm× 20 cm and S2: 60 cm× 20 cm and eight different fertilizer dose viz., F1: Urea, TSP and MoP @ 195, 75 and 169 kgha-1 (2 splits of Urea and MoP), F2: Urea, TSP and MoP @ 195, 75 and 169 kgha-1 (3 splits of Urea and MoP), F3: Urea, TSP, MoP and Cowdung @ 260, 100, 225 kgha-1 and 10 tha-1 (2 splits), F4: Urea, TSP, MoP and Cowdung @ 260, 100, 225 kgha-1 and 10 tha-1 (3 splits), F5: Urea, TSP, MoP and Cowdung @ 260, 100, 225 kgha-1 and 5 tha-1 (2 splits), F6: Urea, TSP, MoP and Cowdung @ 260, 100, 225 kgha-1 and 5 tha-1 (3 splits), F7: Urea, TSP, MoP and Cowdung @ 195, 75, 169 kgha-1 and 10 tha-1 (2 splits), and F8: Urea, TSP, MoP and Cowdung @ 195, 75, 169 kgha-1 and 10 tha-1 (3 splits). The highest leaf number (35.80), shoot length (45.17 cm), root length (38.17 cm), girth (44.33 cm), root dry weight (132.33 g), root yield (86.87 tha-1) and total soluble solid (18.20%) was recorded in the 50cm × 20cm spacing along with application of Urea, TSP, MoP and Cowdung @ 260, 100, 225 kg and 10 tha-1, respectively with 3 splits of Urea & MoP (S1 × F4 combination) followed by 60cm × 20cm spacing along with application of Urea, TSP, MoP and Cowdung @ 260, 100, 225 kg and 10 tha-1, respectively with 3 splits of Urea & MoP (S2 × F4 combination) where leaf number (35.13), shoot length (44.97 cm), root length (38.47 cm), girth (43.90 cm), root dry weight (120.17 g), root yield (88.97 tha-1) and total soluble solid (18.12%) was obtained which were statistically significant and superior as compared to other treatment combinations. [Fundam Appl Agric 2024; 9(4.000): 266-276]